2020
DOI: 10.1111/jgh.15022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low‐dose versus high‐dose simethicone with polyethylene glycol for bowel preparation: A prospective randomized controlled trial

Abstract: Li-sheng Wang and Jun Yao were responsible for design of the study and reviewed the manuscript. De-Feng Li, Ming-han Luo and Feng Xiong drafted the manuscript. Qing-qing Du, Hai-yang Zhang, Ting-ting Liu and Rui-yue Shi recorded the data. Ming-guang Lai, Ying-xue Li, Yan-hui Tian, Ben-hua Wu and Su Luo performed the data analysis. De-feng Li, Yang Song, Zheng-lei Xu and Ding-guo Zhang performed colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
(70 reference statements)
2
13
1
Order By: Relevance
“…In the subgroup analysis, we compared the effect of low-dose simethicone (< 400 mg) to that of high-dose simethicone (≥ 400 mg) for the ADR and PDR. Our results revealed that simethicone at a high or low dose made no significant difference in terms of ADR and PDR, suggesting that the low dose was not inferior to the high dose, similar to the study of Li et al [ 45 ]. Further research is required to determine the optimal dose of simethicone in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…In the subgroup analysis, we compared the effect of low-dose simethicone (< 400 mg) to that of high-dose simethicone (≥ 400 mg) for the ADR and PDR. Our results revealed that simethicone at a high or low dose made no significant difference in terms of ADR and PDR, suggesting that the low dose was not inferior to the high dose, similar to the study of Li et al [ 45 ]. Further research is required to determine the optimal dose of simethicone in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…In the subgroup analysis, we compared the effect of the low dose simethicone (< 400 mg) versus that of high dose simethicone (≥ 400 mg) for ADR and PDR. Our results also revealed that simethicone with high or low dose had no signi cant difference of ADR and PDR, suggesting that the low-dose simethicone was not inferior to the high-dose one in terms of ADR and PDR, which is similar to the study of Li et al [39]. Although residual simethicone in biopsy channels could promote bio lm formation [40], simethicone adding to PEG solution could decrease the infection risk of endoscope-transmission [31].However, the optimal dose of SIM is yet to be ascertained [41].…”
Section: Discussionsupporting
confidence: 91%
“…Bowel preparation was administered as previously described [12]. In the SIM evening group, the patients were instructed to consume 200 mg SIM (Berlin-Chemie AG, Berlin, Germany) in addition to 1L PEG (Shenzhen Wan he Pharmaceutical Co. Ltd, Shenzhen, China) at 7 PM on the day prior to colonoscopy, and the remaining 1L PEG was ingested in the morning 5 hours before colonoscopy.…”
Section: Bowel Preparationmentioning
confidence: 99%
“…Moreover, several studies have reported that simethicone (SIM), as an antifoaming agent, combined with PEG for bowel preparation can improve bowel preparation quality and patients' tolerance [10,11]. Meanwhile, we discovered that the addition of low-dose SIM (200 mg) to split-dose 2L PEG was as effective as the addition of high-dose SIM (1200 mg) with respect to adequate bowel preparation, ADR, and patients' tolerance in a Chinese population [12]. However, the optimal time of simethicone addition to PEG for bowel preparation remains undetermined.…”
Section: Introductionmentioning
confidence: 99%